(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: soluble interleukin-2 receptor (sIL-2R) is secreted by lymphocytes upon activation and has been used as a marker of immune activation in several diseases. Objective: This study aimed to assess the potential clinical utility of serum level of serum soluble interleukin-2 receptor (sIL-2R) as a diagnostic tool in rheumatoid arthritis disease (RA). The study investigated also the association between serum sIL-2R levels with other parameters used for assessment of RA such as rheumatoid factor (RF), erythrocytes sedimentation rate (ESR), C-reactive protein (CRP), and uric acid. Methods: Serum sIL-2R levels, measured by ELISA, were evaluated in 25 RA patients who have positive rheumatoid factor (RF) and compared with those of 25 normal controls. The correlations with the other parameters were analyzed. Results: Compared with the healthy control group, RA patients tended to have significantly higher serum sIL-2R and ESR concentrations (P6mg/dl) was found in 56% of patients. The sIL-2R level was positively correlated with RF and ESR, while a slight positive correlation with uric acid was noticed. Serum sIL-2R showed a high sensitivity and specificity for the patients with positive RF. Conclusions: A sIL-2R level is a sensitive and specific marker and can be useful for diagnosis of RA. Key words: C-reactive protein, Erythrocyte sedimentation rate, Rheumatoid arthritis, Soluble interleukine-2 receptors.